2008
DOI: 10.1016/j.pneurobio.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

It is not “either/or”: Activation and desensitization of nicotinic acetylcholine receptors both contribute to behaviors related to nicotine addiction and mood

Abstract: Nicotine can both activate and desensitize/inactivate nicotinic acetylcholine receptors (nAChRs). An ongoing controversy in the field is to what extent the behavioral effects of nicotine result from activation of nAChRs, and to what extent receptor desensitization is involved in these behavioral processes. Recent electrophysiological studies have shown that both nAChR activation and desensitization contribute to the effects of nicotine in the brain, and these experiments have provided cellular mechanisms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
346
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(359 citation statements)
references
References 168 publications
(240 reference statements)
11
346
1
1
Order By: Relevance
“…143 Molecular function of neuronal nAChRs in ND: pharmacological and biochemical aspects A wide range of neuropsychopharmacological data support the notion that ND involves more than one specific nicotinic receptor subtype (for recent comprehensive reviews see: Rose 16 ; Picciotto et al). 159 This supports our hypothesis that different variants in multiple neuronal nAChR subtypes may mediate genetic vulnerability to ND. The addiction process is complicated, and depends on many factors including pharmacological characteristics of the receptor such as differential affinity for nicotine, subunit composition and stoichiometry.…”
Section: Chrna7supporting
confidence: 87%
See 1 more Smart Citation
“…143 Molecular function of neuronal nAChRs in ND: pharmacological and biochemical aspects A wide range of neuropsychopharmacological data support the notion that ND involves more than one specific nicotinic receptor subtype (for recent comprehensive reviews see: Rose 16 ; Picciotto et al). 159 This supports our hypothesis that different variants in multiple neuronal nAChR subtypes may mediate genetic vulnerability to ND. The addiction process is complicated, and depends on many factors including pharmacological characteristics of the receptor such as differential affinity for nicotine, subunit composition and stoichiometry.…”
Section: Chrna7supporting
confidence: 87%
“…As receptor desensitization (decreased response to agonist) and upregulation after chronic nicotine exposure (with potential for increased response to agonist) act in opposite directions, these mechanisms seem compensatory to each other. 159 So far only very limited research has been carried out regarding the possible influence of identified genetic variants in nAChR-encoding genes on these pharmacological traits. In the following section, we point out possible mechanism by which neuronal nAChR variants may influence the pharmacological profile of the subunits and of the receptor subtypes containing them.…”
Section: Chrna7mentioning
confidence: 99%
“…Recent studies showed that nAChR agonists (e.g., nicotine) attenuate LIDs, especially when striatal dopamine transmission is relatively intact 10, 33. This effect is believed to occur through desensitization of nAChRs, with a consequent decline in nAChR‐mediated function,34 and release of glutamate from cortical and thalamic afferent 35, 36. Notably, in comparison to the putamen, the dopaminergic innervation of the caudate nucleus is partially preserved in mild‐moderate subjects with PD, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this work, we will be focusing on the a4b2 heteromeric receptor in terms of its translational importance. In contrast to other subtypes, the a4b2 nAChR subtype has been shown to readily up-regulate following chronic exposure to nicotine, as evidenced by findings in cell culture (Xiao and Kellar 2004), rodents (Schwartz and Kellar 1983;Marks et al 1985), monkeys (Picciotto et al 2008), and humans (Mukhin et al 2008). The up-regulation of receptors in the face of increased agonist is a characteristic unique to nicotine, and its full importance is not understood.…”
Section: Neurochemisty Of Nicotinementioning
confidence: 99%